2020
DOI: 10.1097/aud.0000000000000948
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Lockdown Affects Hearing Disability and Handicap in Diverse Ways: A Rapid Online Survey Study

Abstract: The aim of this study was to explore the perceived effects of coronavirus disease 2019 (Covid-19) social distancing restrictions and safety measures on people with hearing loss. Design: Participants were 129 adults (48.1% female, mean age 64.4 years) with an audiometric hearing loss, living in Glasgow, Scotland. A rapidly deployed 24-item online questionnaire asked about the effects of certain aspects of lockdown, including face masks, social distancing, and video calling, on participants' behavior, emotions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
101
0
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(132 citation statements)
references
References 10 publications
12
101
0
19
Order By: Relevance
“…Anxiety levels measured using GAD-7 were not significantly associated with SSQ12 scores. This is in keeping with results from a recent survey that demonstrated that during the pandemic, almost 70% of people with worse hearing felt relief not to be obliged to attend social gatherings (Naylor, Burke, and Holman 2020). Therefore, for some people with HL who may struggle with group conversations, the enforced distancing has meant a reduction in anxiety regarding attending social gatherings and communication in noisy public areas.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Anxiety levels measured using GAD-7 were not significantly associated with SSQ12 scores. This is in keeping with results from a recent survey that demonstrated that during the pandemic, almost 70% of people with worse hearing felt relief not to be obliged to attend social gatherings (Naylor, Burke, and Holman 2020). Therefore, for some people with HL who may struggle with group conversations, the enforced distancing has meant a reduction in anxiety regarding attending social gatherings and communication in noisy public areas.…”
Section: Discussionsupporting
confidence: 86%
“…com/doi/suppl. Due to the time pressures to collect the data during the COVID-19 pandemic, best practice methodology, such as validation of this measure, was relaxed in the interest of speed, as were the case with other COVID-19 related research (Geldsetzer 2020;Naylor, Burke, and Holman 2020;Saunders and Roughley 2020). Participants were asked to complete the measure twice, as they would have "before lockdown" as well as in their current situation.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential negative impact of face masks on communication in general has recently been appointed in the popular press and in scientific literature 4‐9 . Most of these papers address the problem from the perspective of the patient—health worker relationship.…”
Section: Introductionmentioning
confidence: 99%